Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-91623-3
|View full text |Cite
|
Sign up to set email alerts
|

YIV-906 potentiated anti-PD1 action against hepatocellular carcinoma by enhancing adaptive and innate immunity in the tumor microenvironment

Abstract: YIV-906 (PHY906) is a standardized botanical cancer drug candidate developed with a systems biology approach—inspired by a traditional Chinese herbal formulation, historically used to treat gastrointestinal symptoms including diarrhea, nausea and vomiting. In combination with chemotherapy and/or radiation therapy, preclinical and clinical results suggest that YIV-906 has the potential to prolong survival and improve quality of life for cancer patients. Here, we demonstrated that YIV-906 plus anti-PD1 could era… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
(48 reference statements)
0
21
0
Order By: Relevance
“…In addition, the combination of TCM with ICIs, other chemotherapeutic drugs and molecular targeted drugs improved the antitumor effect of the drugs [ 108 113 ] (Additional file 1 : Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the combination of TCM with ICIs, other chemotherapeutic drugs and molecular targeted drugs improved the antitumor effect of the drugs [ 108 113 ] (Additional file 1 : Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Yang and his team reported that the anti-tumor activity of anti-PD1 was markedly enhanced in combination of YIV-906 via promoting the adaptive and innate immune responses. 279 In terms of single herbs, Kanglaite as an extract from Coix seeds also enhanced the suppressive effects of cisplatin on HCC cells, exhibiting synergistic effects in the combination with conventional treatments. 280 Of significant mention is icaritin, a prenylflavonoid derivative from epimedium.…”
Section: Treatment Advances In Systemic Therapymentioning
confidence: 99%
“…In the presence of neoantigens caused by anti-cancer agents, YIV-906 could potentiate innate and/or adaptive immunity potentiation through multiple mechanisms of action. To enhance innate immunity, YIV-906 can potentiate interferon-gamma (IFNg) action to induce M1-like macrophage polarization simultaneously inhibiting IL4 action to induce M2 macrophage polarization ( Lam et al, 2015 ; Yang et al, 2021 ). To enhance adaptive immunity, YIV-906 reduces PD1 or counteracts PD-L1 induction caused by anti-PD1, leading to higher T-cell activation-associated gene expression in the tumor ( Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To enhance innate immunity, YIV-906 can potentiate interferon-gamma (IFNg) action to induce M1-like macrophage polarization simultaneously inhibiting IL4 action to induce M2 macrophage polarization ( Lam et al, 2015 ; Yang et al, 2021 ). To enhance adaptive immunity, YIV-906 reduces PD1 or counteracts PD-L1 induction caused by anti-PD1, leading to higher T-cell activation-associated gene expression in the tumor ( Yang et al, 2021 ). To help overcome immune suppression, YIV-906 reduces immune tolerance by modulating IDO activity and reducing monocytic MDSC in the tumor ( Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%